Workshop Teknologi Metaverse Sebagai Media Pembelajaran - Heni Sulistiani; Auliya Rahman Isnain; Yuri Rahmanto; Very Hendra Saputra; Priskilia Lovika; Rido Febriansyah; Ady Chandra (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2023)
Metaverse is a virtual space where one can interact directly with the real world. In the Education 5.0 era, the use of metaverse technology as a learning medium has begun to be used in the learning process. Using metaverse technology can explain an abstract concept as if it were real with the virtual reality and augmented reality facilities contained in the metaverse, thus, it is likely that learning outcomes will be better than using conventional learning media. However, not all levels of education know and can use this technology. This Community Service activity was carried out at Candipuro State Vocational School, South Lampung to introduce virtual reality and augmented reality-based metaverse technology to students with the aim of students knowing and being able to use the metaverse as a learning medium. The material given in this activity is a workshop in the form of a basic introduction to the metaverse. Students are very enthusiastic in learning this metaverse technology. Based on the results of the questionnaires given to students before and after the workshop, there was an increase related to metaverse knowledge